Antibacterial action of the essential oil of leaves of Eucalyptus globulus, against multiresistant pathogens / Ação antibacteriana do oléo essencial das folhas de Eucalyptus globulus, frente a patógenos multirresitentes - Carla Vanessa Ribeiro Lima; Felipe José Mathias das Neves; Lucas Pedrosa Souto Maior; Luana Luzia Santos Pires; Thiago José Matos-Rocha; Aldenir Feitosa dos Santos (Universidade Estadual de Alagoas, 2019)
The increase of the bacteria resistance has aroused the interest in the use of essential oils as antimicrobial sources. With that, the main goal of this paper was to evaluate the antibacterial activity in the essential oil from the leaves of Eucalyptus globulus in bacteria that causes hospital infections. The oil was first tested in the concentration of 8%, from which were performed dilutions until 0,0625% in order to determine the minimum inhibitory concentration (MIC). The oil showed inhibition action when faced with multiresistants bacteria, with only one exception from the Pseudomonas aeruginosa, with the smallest MIC to Staphylococcus Aureus oxacillin resistants, what it comes to conclusion is that the essential oil represents a new therapeutic source against hospital infectious bacteria.